Effect of Italy's motorcycle helmet law on traumatic brain injuries. Issue 3 (9th September 2003) - Servadei, F; Begliomini, C; Gardini, E; Giustini, M; Taggi, F; Kraus, J
Abstract : Objectives: To evaluate the impact of a revised Italian motorcycle-moped-scooter helmet law on crash brain injuries. Design: A pre-post law evaluation of helmet use and traumatic brain injury (TBI) occurrence from 1999 to 2001. Setting: Romagna region, northeastern Italy, with a 2000 resident population of 983 534 persons. Participants: Motorcycle-moped rider survey for helmet use compliance and all residents in the region admitted to the Division of Neurosurgery of the Maurizio Bufalini Hospital in Cesena, Italy for TBI. Outcome measures: Helmet use compliance and change in TBI admissions and type(s) of brain lesions. Results: Helmet use increased from an average of less than 20% to over 96%. A comparison of TBI incidence in the Romagna region shows that there was no significant variation before and after introduction of the revised helmet law, except for TBI admissions for motorcycle-moped crashes where a 66% decrease was observed. In the same area TBI admissions by age group showed that motorcycle mopeds riders aged 14–60 years sustained significantly fewer TBIs. The rate of TBI admissions to neurosurgery decreased by over 31% and epidural hematomas almost completely disappeared in crash injured moped riders. Conclusions: The revised Italian mandatory helmet law, with police enforcement, is an effective measure for TBI prevention at all ages.